2021
DOI: 10.3390/ijerph18168575
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Experience and Perception of Gender-Based Violence Health Services: A Mixed Methods Study on Adolescent Girls and Young Women in Tanzania

Abstract: Many adolescent girls and young women (AGYW) experience gender–based violence (GBV) in Tanzania and only few seek GBV health services following violence. The objectives of our study are (1) to evaluate knowledge of gender–based violence among AGYW, (2) to explore their perceptions of and experiences with GBV health service quality and (3) to evaluate access to comprehensive GBV services. This study employed an explanatory, sequential mixed methods design in two districts of Dar es Salaam, Tanzania (Kinondoni a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 44 publications
2
18
2
Order By: Relevance
“…In the case of domestic violence, mediation within the family or with community leaders is the preferred option. In terms of GBV management, other authors highlight the limited availability of health services for GBV and the low use of these services like in Tanzania [28]. Many studies have noted, as in our results, the silence of married women, which is the result…”
Section: Women's Attitudes Towards Gbvsupporting
confidence: 56%
“…In the case of domestic violence, mediation within the family or with community leaders is the preferred option. In terms of GBV management, other authors highlight the limited availability of health services for GBV and the low use of these services like in Tanzania [28]. Many studies have noted, as in our results, the silence of married women, which is the result…”
Section: Women's Attitudes Towards Gbvsupporting
confidence: 56%
“…Interestingly, some cultural and social norms may perpetrate specific forms of violence. A study conducted in Tanzania reported that AGYW expressed that men have a right to control or discipline women through physical means, and women’s acceptance of this made them more vulnerable to continued violence [ 32 ]. This purports that cultural and social norms value men as superior and more powerful than women, and these norms and cultures subordinate women in many life spheres, from economic independence to decision-making power.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, for practical reasons and the researcher’s preference (Klem et al , 2021), no specific software beyond Microsoft Word was used. Similar to previous studies (Irimiás et al , 2021; Mtaita et al , 2021), the author performed manually qualitative analyses using Microsoft Word. The author carried out three main steps in analysis: open coding, axial coding and selective coding, as suggested by Strauss and Corbin (1990) and described in Section 4.2.…”
Section: Methodsmentioning
confidence: 99%